DEEP FAKE: How to Determine if a Doctored Photograph, Video, or Audio Recording is Real. - REDMOND, TIM (Skeptic, 2022)
The article discusses about the terrorist attacks of September 11, 2001, an email containing a photograph from a camera allegedly found in the rubble remains of the twin towers began to circulate online. It also highlights The snapshot, which featured an unsuspecting tourist posing for a picture on the roof of the World Trade Center as a hijacked airliner approached in the distance,.